Evaluasi Program Pendidikan: Tinjauan Terhadap Efektivitas dan Tantangan - Rahmawati, Indri Septianur (El-Idare, 2023)
The evaluation of educational programs plays a crucial role in enhancing the quality of education but faces complex challenges. Literature research reveals several key issues, including determining appropriate evaluation criteria, measuring long-term impact, and integrating non-academic aspects. Complexity arises from cultural and educational system differences across contexts. Evaluation models like CIPP and Kirkpatrick provide frameworks, yet their implementation requires adaptation to varying contextual aspects. Solutions to these challenges involve developing evaluation capacities at the school level, active stakeholder participation, and the formation of comprehensive evaluation policies. Effective educational program evaluation necessitates an adaptive, creative, and participation-based approach, aiming to contribute positively to the overall improvement of education quality.